Tinjauan Psak 72 Terhadap Koreksi Perpajakan pada Perusahaan Konstruksi (PT XYZ) - Muhammad Rheza Ramadhan; Fina Yulia Markay (Journal of Financial and Tax, 2021)
Tax calculation on construction company with different revenue recognition method when some of construction services performed simultaneously will generate different amounts of tax payable. This can be used by construction companies to reduce final taxes or can be used by the government as an opportunity to expand state revenues from the tax sector. The difference between allocation approach of the transaction price 1) 1) Adjustment Market Assessment Approach; 2) Expected Cost Plus A Margin Approach; and 3) Residual Approach, which used when the bundling contract applied different final tax rates (planning services and supervision services with execution services) will result in different taxes payable.